IMPROVING LISTENING SKILL WITH A VIDEO BASED PODCAST FOR VOCATIONAL HIGH SCHOOL STUDENTS’ - Valentin, Oktavia (Journal of English Teaching and Learning, 2024)
This study aims to improve students' listening skills using video podcast media in class XI students of vocational high school based in Banyuwangi. This study used a pre-experimental design with a pre-test and post-test model in one group. Data were collected through observation, pre test, and post-test. The results showed a significant improvement in students' listening skills after being given treatment using video podcasts. The average pre-test score was 67, while the post-test score increased to 87, with an increase of 30%. The t-test results showed a value of 5.45 which was greater than the t-table value (1.833), indicating a significant difference between the pre-test and post-test. The use of video podcasts as learning media helps students understand pronunciation, improve material comprehension, and build confidence in listening. Thus, this media can be an effective alternative to improve students' listening skills. The researcher recommends using video podcasts with interesting topics to increase students' learning motivation.